Compact and Broadband-Balanced Amplifier for a Monolithic Microwave Integrated Circuit Using Lumped Elements Only - Heeje Han; Hongjoon Kim (International Journal of Antennas and Propagation)
A flat phase difference across a broad bandwidth is achieved by appropriately combining the positive and negative phase propagation of right-handed (RH) and left-handed (LH) transmission lines (TLs), respectively. Employment of lumped elements provides easy realization of both TLs with the desired frequency passband, characteristic impedance, and phase propagation. The proposed quadrature power divider (QPD) was fabricated in a compact size by only using lumped elements instead of general TLs with a large area and a narrow bandwidth. The fabricated QPD maintains a flat phase difference of 90° ± 8.7° over a frequency range of 1.19–2.96 GHz while its circuit size is 0.036 λg2. Owing to drastic size reduction of the QPD, the proposed balanced amplifier (BA) also could be realized with an extremely compact size of 0.044 λg2 and broad bandwidth unlike in other BAs reported in the literature and maintains a return loss of less than −10 dB at each port over the bandwidth of the QPD.